"Generally, I live a lie": Transgender consumer experiences and responses to symbolic violence. Issue 4 (27th August 2022) - Duncan‐Shepherd, Sophie; Hamilton, Kathy
Abstract: In this article, our focus is on how trans consumers experience symbolic violence to draw attention to inequalities that may otherwise remain hidden. Unlike overt acts of physical violence, symbolic violence is subtle and occurs routinely throughout the course of everyday life. We address the following research questions: how do trans consumers experience symbolic violence, what are their responses to this, and what impact does this have on their wellbeing? Our findings demonstrate that symbolic violence functions at sociocultural, interpersonal, and individual levels for trans consumers. We illustrate the tensions trans people encounter between conforming to cisgender hegemony and living an 'authentic' life. The subtle, naturalizing power and misrecognition of symbolic violence appears challenging for the wellbeing of transgender consumers. The lens of symbolic violence usefully informs and integrates with the consumer vulnerability perspective that has previously been used as a theoretical framework to understand transgender consumers' experiences.